External Validation of a Clinical Nomogram for Predicting Intracranial Hematoma Following Head Computed Tomography in Pediatric Traumatic Brain Injury - Jongjit, Apisorn; Tunthanathip, Thara (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Over-investigation of head computed tomography (CT) has been observed in children with TBI. Long-term effects from a head CT brain scan have been addressed and those should be balanced. A nomogram is a simple prediction tool that has been reported for predicting intracranial injuries following a head CT of the brain in TBI children in literature. This study aims to validate the performance of the nomogram using unseen data. Additionally, the secondary objective aims to estimate the net benefit of the nomogram by decision curve analysis (DCA).Methods We conducted a retrospective cohort study with 64 children who suffered from traumatic brain injury (TBI) and underwent a CT of the brain. Nomogram's scores were assigned according to various variables in each patient; therefore sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy and F1 score were estimated by the cross-tabulation of the actual results and the predicted results. Additionally, the benefits of a nomogram were compared with “None” and “All” protocols using DCA.Results There were 64 children with TBI who underwent a head CT in the present study. From the cross-tabulation, the nomogram had a sensitivity of 0.60 (95%CI 0.29–0.90), specificity of 0.96 (0.91–1.0), PPV of 0.75 (0.44–1.0), NPV of 0.92 (0.86–0.99), accuracy of 0.90 (0.83–0.97), and an F1 score of 0.66 (0.59–0.73). Also, the area under the curve was 0.78 which was defined as acceptable performance. For the DCA at 0.1 high-risk threshold, the net benefit of the nomogram was 0.75, whereas the “All” protocol had the net benefit of 0.40 which was obviously different.Conclusion A nomogram is a suitable method as an alternative prediction tool in general practice that has advantages over other protocols.
Keywords: External validation; Nomogram; intracranial hematoma; pediatric traumatic brain injury; head injury